Transformation of the Museum in the 21st Century: Baltic States Museums Visitors - Miežietytė-Gudzinskė, Alina; Jurėnienė, Virginija (Vilnius University Open Series, 2021)
Audience development in cultural organisations and museums in Lithuania is relevant and not enough explored. While reading different academic literature and research on this topic, the most common issue mentioned is a lack of research about visitors to Lithuanian cultural organisations and museums. Most usually, communication about events and products created for visitors is based on the intuition or opinion of the employees, rather than on analysis of visitor’s expectations. Meanwhile, global research is orientated to understand, who is the audience of the organisation and what expectations it has. Those studies show that the audience is expecting to get new emotions, learn new things, new experiences, and increase social connections, to feel welcomed and interested.